Gender Subversion in Syair Khadamuddin: A Gynocritical Study of Sabariah's Character - Nureza Dwi Anggraeni; Zuriyati; Eva Leiliyanti, (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2026)
This study investigates the subversion of gender norms in Syair Khadamuddin, a 19th-century Malay narrative poem authored by Aisyah Sulaiman, through a gynocritical framework that emphasizes dialogic exchanges among female characters. The research addresses the problem of patriarchal dominance in classical Malay literature, which typically marginalizes women’s voices and upholds male-centered moral codes. In contrast, this rare female-authored syair offers a distinctive portrayal of women who actively negotiate their roles in relation to marriage, sexuality, morality, and obedience. Guided by Elaine Showalter’s gynocriticism, the study focuses on dialogic episodes in which women critique their husbands’ behavior, question the limits of obedience within Islamic and social contexts, and share their personal experiences. Using textual analysis, the research uncovers moments of female agency, where moral reasoning and collective consciousness emerge as acts of subtle resistance. The findings reveal that the character Sabariah, alongside other women, constructs a counter-narrative of female virtue based on ethical deliberation rather than passive submission. These female-centered dialogues challenge the conventional representation of women as silent or subordinate, positioning the syair as a dialogic space of empowerment. The study concludes that Syair Khadamuddin exemplifies how classical texts authored by women can inscribe gendered resistance from within patriarchal genres, thus enriching feminist literary discourse.